2019
DOI: 10.4314/ajcem.v20i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasmosis and associated risk factors in pregnant women at the Protestant Hospital, Mbouo-Bandjoun, Cameroon

Abstract: Background: Toxoplasmosis is a common worldwide infection caused by the protozoan Toxoplasma gondii. In Cameroon, several recent studies have reported high seroprevalence of this parasitosis in various hospitals (Douala, Limbe, Njinikom and Yaoundé). The aim of this study was to determine whether this high prevalence of toxoplasmosis might occur in other regions of the country. Methodology: Serological tests by the indirect Enzyme Linked Immunosorbent Assay (ELISA) for IgG and IgM were carried out on 200 pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
10
3
Order By: Relevance
“…In Cameroon, the seroprevalence was similar to a recent (78.6%) study in Douala [ 22 ] and an earlier study in Yaoundé (77.1%). [ 25 ] On the other hand, the seroprevalence obtained in this study is substantially higher than most studies within Cameroon: 54.5% in Njinikom, North West Region, [ 24 ] 70% in Yaoundé [ 23 ], 32.5% in Buea [ 27 ], and 45.5% in Mbouo-Bandjoun, West Region [ 26 ]. Such variations in the seroprevalence of toxoplasmosis may be due to differences in geographical locations, characteristics of the pregnant women such as age, educational level, handling of cats, hygiene, and feeding-related practices of toxoplasmosis.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In Cameroon, the seroprevalence was similar to a recent (78.6%) study in Douala [ 22 ] and an earlier study in Yaoundé (77.1%). [ 25 ] On the other hand, the seroprevalence obtained in this study is substantially higher than most studies within Cameroon: 54.5% in Njinikom, North West Region, [ 24 ] 70% in Yaoundé [ 23 ], 32.5% in Buea [ 27 ], and 45.5% in Mbouo-Bandjoun, West Region [ 26 ]. Such variations in the seroprevalence of toxoplasmosis may be due to differences in geographical locations, characteristics of the pregnant women such as age, educational level, handling of cats, hygiene, and feeding-related practices of toxoplasmosis.…”
Section: Discussioncontrasting
confidence: 54%
“…On the other hand, no significant associations were found between marital, professional, and HIV statuses, history of abortion, gravidity and parity, water source, eating grilled meat, tasting undercooked meat, presence of cats at home or in the neighbourhood, and Toxoplasma antibody seropositivity in the current study. However, some factors were found to be statistically significant in other similar studies: presence of cats at home and history of abortion in Ethiopia [ 47 ], HIV status in West Cameroon [ 26 ], and source of drinking water in Douala, Cameroon [ 23 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This prevalence is similar to that obtained by Nissapatorn, et al [10] in Thailand (23.1%). The seroprevalence obtained in this study is lower than in most studies conducted in Cameroon: 34.5% in the Bamenda Regional Hospital [11], 32.5% in Buea [12], and 45.5% in Mbouo-Bandjoun, Western Region of Cameroon [6]. Such variations in toxoplasmosis seroprevalence may be due to differences in geographical location, characteristics of pregnant women such as age, educational level, cat handling, hygienic and feeding habits.…”
Section: Discussioncontrasting
confidence: 74%
“…Pregnant women who are not immunized (negative serology to IgG and Ig M anti-toxoplasmic antibodies) constitute an important risk group. In Cameroon, recent studies have reported seroprevalences of 45.5% in Mbou'o-Bandjoun [6], 71.8% in Limbe [7], 78.6% in the city of Douala [8] and 80% in the city of Yaoundé [9]. Although toxoplasmosis serology is among the examinations for the first prenatal consultation, pregnant women at the Bamenda regional hospital neglect this examination because of the lack of knowledge about toxoplasmosis and the high cost of this examination.…”
Section: Resultsmentioning
confidence: 99%